On the atmospheric budget of 1,2-dichloroethane and its impact on stratospheric chlorine and ozone (2002–2020) - R. Hossaini; D. Sherry; Z. Wang; Z. Wang; M. P. Chipperfield; M. P. Chipperfield; W. Feng; W. Feng; D. E. Oram; D. E. Oram; K. E. Adcock; S. A. Montzka; et al. (Atmospheric Chemistry and Physics)
The chemical compound 1,2-dichloroethane (DCE), or ethylene dichloride, is an industrial very short-lived substance (VSLS) whose major use is as a feedstock in the production chain of polyvinyl chloride (PVC). Like other chlorinated VSLSs, transport of DCE (and/or its atmospheric oxidation products) to the stratosphere could contribute to ozone depletion there. However, despite annual production volumes greatly exceeding those of more prominent VSLSs (e.g. dichloromethane), global DCE observations are sparse; thus, the magnitude and distribution of DCE emissions and trends in its atmospheric abundance are poorly known. In this study, we performed an exploratory analysis of the global DCE budget between 2002 and 2020. Combining bottom-up data on annual production and assumptions around fugitive losses during production and feedstock use, we assessed the DCE source strength required to reproduce atmospheric DCE observations. We show that the TOMCAT/SLIMCAT 3-D chemical transport model (CTM) reproduces DCE measurements from various aircraft missions well, including HIPPO (2009–2011), ATom (2016–2018), and KORUS-AQ (2016), along with surface measurements from Southeast Asia, when assuming a regionally varying production emission factor in the range of 0.5 %–1.5 %. Our findings imply substantial fugitive losses of DCE and/or substantial emissive applications (e.g. solvent use) that are poorly reported. We estimate that DCE's global source increased by ∼ 45 % between 2002 (349 ± 61 Gg yr−1) and 2020 (505 ± 90 Gg yr−1), with its contribution to stratospheric chlorine increasing from 8.2 (± 1.5) to ∼ 12.9 (± 2.4) ppt Cl (where ppt denotes parts per trillion) over this period. DCE's relatively short overall tropospheric lifetime (∼ 83 d) limits, although does not preclude, its transport to the stratosphere, and we show that its impact on ozone is small at present. Annually averaged, DCE is estimated to have decreased ozone in the lower stratosphere by up to several parts per billion (< 1 %) in 2020, although a larger effect in the springtime Southern Hemisphere polar lower stratosphere is apparent (decreases of up to ∼ 1.3 %). Given strong potential for growth in DCE production tied to demand for PVC, ongoing measurements would be of benefit to monitor potential future increases in its atmospheric abundance and its contribution to ozone depletion.